Fe/Co/N–C/graphene derived from Fe/ZIF-67/graphene oxide three dimensional frameworks as a remarkably efficient and stable catalyst for the oxygen reduction reaction. Issue 4 (18th January 2022) - Xiong, Junchao; Chen, Xiaohong; Zhang, Yupan; Lu, Yue; Liu, Xundao; Zheng, Yafei; Zhang, Yongming; Lin, Jun
Abstract : Fe/Co/N–C/graphene was facilely and successfully prepared by a calcination process, which has remarkable electrocatalytic ORR activity in alkali solutions and also displays an exceptional stability for the ORR and methanol tolerance. Abstract : The development of non-noble metal catalysts with high-performance, long stability and low-cost is of great importance for fuel cells, to promote the oxygen reduction reaction (ORR). Herein, Fe/Co/N–C/graphene composites were easily prepared by using Fe/ZIF-67 loaded on graphene oxide (GO). The Fe/Co/porous carbon nanoparticles were uniformly dispersed on graphene with high specific surface area and large porosity, which endow high nitrogen doping and many more active sites with better ORR performance than the commercial 20 wt% Pt/C. Therefore, Fe/Co/N–C/graphene composites exhibited excellent ORR activity in alkaline media, with higher initial potential (0.91 V) and four electron process. They also showed remarkable long-term catalytic stability with 96.5% current retention after 12 000 s, and outstanding methanol resistance, compared with that of 20 wt% Pt/C catalysts. This work provides an effective strategy for the preparation of non-noble metal-based catalysts, which could have significant potential applications, such as in lithium–air batteries and water-splitting devices.